POTENTIAL OF OIL PALM FIBER FROM MILLS WITH A CAPACITY OF 30 AND 60 TONS/H AS A NUTRIENT IN OIL PALM PLANTATIONS - Aldo Dana Asneri Ahmad Lubis; Ika Ucha Pradifta Rangkuti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The palm oil industry produces solid waste in the form of fiber which has been used as boiler fuel, but its potential nutrient content has not been optimally utilized in plantations. This study aims to assess the potential of palm oil fiber from Palm Oil Mills with capacities of 30 and 60 tons/h as a nutrient source for oil palm plants. The study used a quantitative descriptive method to determine differences in nutrient content between mill capacities. The results showed that palm oil fiber from both mill contained the macro nutrients of N, P, K, Mg, and Ca, as well as the micro elements of B, Cu, Zn, Fe, and Mn. Statistical tests showed that most parameters were significantly different (p<0.05) between the two fiber sources. Fiber from the 60 tons/h-mill had a higher N content, making it more potential to support vegetative plant growth. Meanwhile, fiber from a 30 tons/h-mill has higher K, Mg, Ca, and B content, which play important roles in the generative phase. This study concluded that oil palm fiber has the potential to serve as a nutrient source, with an application strategy tailored to the plant's growth phase.